Leaders Enhance Group Members' Work Engagement and Reduce Their Burnout by Crafting Social Identity. (February 2014) - Steffens, Niklas K.; Haslam, S. Alexander; Kerschreiter, Rudolf; Schuh, Sebastian C.; van Dick, Rolf
Previous research has examined burnout and work engagement as a function of demands and resources at work. Yet we know little about the ways in which these are determined by people's social experience as a member of their workgroup as shaped, in particular, by leaders' management of shared identity. To address these issues, we propose a model in which leaders' identity entrepreneurship (the degree to which the leader promotes understanding of shared group identity) impacts on group performance through burnout and work engagement. We tested our model in a field study with 641 participants from the US working population who responded to their workgroup leader and indicated their health. Results indicated that when leaders acted as identity entrepreneurs, group members not only reported higher group performance but also experienced less burnout and were more engaged at work. Moreover, the relationship between identity entrepreneurship and group performance was mediated by an increase in work engagement and a reduction in burnout both of which in turn facilitated group performance. These findings suggest that what it means for health-protective leaders to be 'transformational' is being capable of facilitating the development of a special sense of 'us' that they and group members share.